Profit Sharing System On Clove Commodity: Farmers And Farm Labor In Waipula Negeri Ureng Hamlet, Leihitu District, Central Maluku Regency - Gilang. R. Rumakey; August. E. Pattiselanno; Paul. M. Puttileihalat (International Journal of Economics, Business and Innovation Research, 2024)
The implementation of the clove plantation profit sharing system between farmers and clove farm workers in Waipula Negeri Ureng Hamlet, Leihitu District, Central Maluku Regency, even though it was only done orally (not in writing), without witnesses and the time limit was not specified, has proven to have made a positive contribution to the standard of living and the economy the local community, especially the community in Waipula Hamlet, Ureng State. For this reason, researchers are very interested in conducting further research related to the profit sharing system in Waipula Hamlet with the main problems: 1. What is the profit sharing system between farmers and farm workers on clove plants in Waipula Hamlet?, 2. What is the impact of the clove crop profit sharing system on clove plants? farmers and farm laborers in Waipula Hamlet?. This research was conducted using a qualitative approach method, by conducting interviews and questionnaires directly with 19 respondents. The results of the research show that the form of clove farming production sharing agreement in Leihitu Negeri Ureng District, especially in Waipula Hamlet, is known as "share the two" (Share the Same) 50:50, the mechanism of which is carried out based on an agreement between both parties verbally and on the basis of mutual trust.